Spatial variance analysis of the actual daily mean rainfall in Riyadh for the period 1970 - 2017 - Alanazi, Anoud Radhi Thamer (Journal of natural sciences, life and applied sciences, 2021)
This study aims to compute the actual mean daily rainfall and analyze its statistical characteristics at the stations of Al Majma’ah (R101-460), Riyadh factories (R001-452), Duruma (R112-470), Jubaylah (R106-464), Sudus (R102-461), Rumah (HU103-954, Shaqra’a (R006-457), Hawtat Sudayr (R005-456), Al Hariq (R104-453), and Huraymilah (R103-462). To achieve the objectives, this study relied on the inductive approach with analyzing the statistical characteristics of rainfall distribution by applying dispersion measures (mean, standard deviation, standard error of the mean, standard error of standard deviation) and on calculating the ratio between annual rainfall amounts and the total number of rainy days per year. The spatial analysis also uses the homogeneous classes of the annual rainfall, the number of rainy days, and the actual mean daily rainfall. This study reached an analysis of the statistical characteristics of the annual rainfall and the number of rainy days recorded during the period 1970-2017 in a total of 10 rain stations. This data is used in calculating the mean actual daily rainfall and in analyzing the variation of its spatial and temporal distribution. The best model for the correlation (cubic model) between annual rainfall amounts and the number of rainy days was also identified. So, this study presents some recommendations to expand this study method in the various regions of the Kingdom of Saudi Arabia and compare its results with the results of similar studies in various dry and semi-arid regions. These study results can be used in inferring the effects of climate change and employ the actual mean daily of rain in estimating the water balance in Riyadh area and surface water resources during rainy days to benefit from them in various fields and in designing a climatic and hydrological database in the various regions of Saudi Arabia. The implementation of irrigation projects to prevent flood risks can be used these water resources.